Pendekatan Bimbingan Individual dalam Membantu Kesulitan Belajar Anak ADHD di SDIT Al-Ghazali Pamekasan Madura (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
Inclusive education at the elementary school level requires an appropriate approach to support the learning success of students with special needs, including children with Attention Deficit Hyperactivity Disorder (ADHD). This study aims to analyze the effectiveness of the individual guidance approach in helping children with ADHD overcome learning challenges, as well as identifying obstacles and supporting factors in its implementation in elementary school environments. This study uses a qualitative descriptive approach with a case study method at SDIT Al-Ghazali Pamekasan, through data collection techniques in the form of observation, in-depth interviews, and documentation. The subjects of the study were grade 4 teachers and one of the students with ADHD as the main subject. Data were analyzed using data reduction, data presentation, and conclusion drawing methods. The results of the study showed that individual guidance was significantly able to improve learning focus, as well as the social and emotional skills of students with ADHD. This success was greatly influenced by teacher involvement, parental support, and adaptive learning strategies. However, challenges such as limited teacher time, lack of varied learning media, and lack of special training are still obstacles that need to be addressed systematically. These findings contribute to the development of more effective inclusive education strategies, especially in supporting students with attention and behavioral disorders in elementary school environments.